Elastic three-dimensional poly (ε-caprolactone) nanofibre scaffold enhances migration, proliferation and osteogenic differentiation of mesenchymal stem cells - Rampichová, Michala; Chvojka, Jiří; Buzgo, Matej; Prosecká, Eva; Mikeš, Petr; Vysloužilová, Lucie; Tvrdík, D; Kochová, Petra; Gregor, T; Lukáš, David; Amler, Evžen (Cell proliferation, 2013)
OBJECTIVES: We prepared 3D poly (ε-caprolactone) (PCL) nanofibre scaffolds and tested their use for seeding, proliferation, differentiation and migration of mesenchymal stem cell (MSCs). MATERIALS AND METHODS: 3D nanofibres were prepared using a special collector for common electrospinning; simultaneously, a 2D PCL nanofibre layer was prepared using a classic plain collector. Both scaffolds were seeded with MSCs and biologically tested. MSC adhesion, migration, proliferation and osteogenic differentiation were investigated. RESULTS: The 3D PCL scaffold was characterized by having better biomechanical properties, namely greater elasticity and resistance against stress and strain, thus this scaffold will be able to find broad applications in tissue engineering. Clearly, while nanofibre layers of the 2D scaffold prevented MSCs from migrating through the conformation, cells infiltrated freely through the 3D scaffold. MSC adhesion to the 3D nanofibre PCL layer was also statistically more common than to the 2D scaffold (P < 0.05), and proliferation and viability of MSCs 2 or 3 weeks post-seeding, were also greater on the 3D scaffold. In addition, the 3D PCL scaffold was also characterized by displaying enhanced MSC osteogenic differentiation. CONCLUSIONS: We draw the conclusion that all positive effects observed using the 3D PCL nanofibre scaffold are related to the larger fibre surface area available to the cells. Thus, the proposed 3D structure of the nanofibre layer will find a wide array of applications in tissue engineering and regenerative medicine.
Keywords: proliferace buněk; tkáňové podpůrné struktury; mezenchymální kmenové buňky; nanovlákna; osteogeneze; povrchové vlastnosti; sialoprotein vázající integrin; Elasticity; buněčná diferenciace; pružnost; lidé; osteokalcin; tkáňové inženýrství; Nanofibers; Osteocalcin; Integrin-Binding Sialoprotein; kultivované buňky; Polyesters; pohyb buněk; Mesenchymal Stem Cells; Regenerative Medicine; Cells, Cultured; Cell Proliferation; Cell Differentiation; Osteogenesis; buněčné kultury; Cell Survival; Cell Movement; Cell Culture Techniques; Tissue Engineering; viabilita buněk; polyestery; Tissue Scaffolds; Surface Properties; regenerativní lékařství; Humans